The impact of physical module (adventure-based activity) of Malaysia's National Service Training Programme on team cohesion - Zakaria, Jaffry; Mariapan, Manohar; Hasbullah, Nor Azlina (Academic Journals, 2013)
The National Service Training Programme better known as Program Latihan Khidmat Negara (PLKN) was launched by the Malaysian government on the 16th of February 2004 to foster national unity and integration. However, since its inception, no specific empirical study has been conducted on the physical activity module (adventure-based activity) to measure the effectiveness of the programme in improving the process of national unity and integration. Modified Group Environment Questionnaire (GEQ) was used to collect the required data which was administered during the pre and post-test at the respective camps. The present research attempts to measure the effectiveness of physical activity module of the programme which consists of the adventure-based activity curriculum and to study the effects of outdoor activities on team cohesion among the participants of the programme at three camps namely, Tasik Meranti, Tasoh and Guar Chenderai Camps in the state of Perlis, Northern Peninsular Malaysia. Pre and post-test were conducted in order to investigate the effects of adventure-based activity on cohesiveness among participants in groups at the camps. Nevertheless, after the physical activity curriculum at the camps was accomplished, team cohesion was successfully developed in all sub-scales investigated. The statistical analysis of GEQ on the pre and post-test proved that team cohesion among the participants was achieved and significantly different. The physical activity module (adventure-based activity) had increased the level of participants’ group cohesiveness and resulted in positive group binding.